CHOICE-BASED CONJOINT ANALYSIS: UM ENFOQUE BAYESIANO - BARBOSA, Eduardo Campana; SILVA, Carlos Henrique Osório; NASCIMENTO, Moysés; SILVA, Fabyano Fonseca e; MINIM, Valéria Paula Rodrigues; DELIZA, Rosires; DELLA LUCIA, Suzana Maria (Brazilian Journal of Biometrics, 2018)
In this paper we present a Bayesian approach to Frequentist Logit Multinomial model used in Choice-Based Conjoint Analysis. The analysis was conducted with data of choice for the assessment by 144 consumers, eight samples of light strawberry flavored yogurts, ranging information from three ingredients (sugar, fat and protein) in a full factorial design. The results and inferences obtained by the Bayesian approach are presented in terms of estimating the main effect of the attributes, the choice probabilities and choice ratio. The Frequentist results are also reported and discussed. The Bayesian analysis showed similar results to Frequentist and allowed the construction of credibility intervals for choice probabilities and choice ratio, allowing statistically compare such quantities. About the practical results, the most likely choice was associated with yoghurt containing strawberry flavor light information "0% sugar", "0% fat" and "bioactive proteins enriched".